2016
DOI: 10.1002/humu.23041
|View full text |Cite
|
Sign up to set email alerts
|

Coagulation Factor XIIIA Subunit Missense Mutations Affect Structure and Function at the Various Steps of Factor XIII Action

Abstract: Inherited defects of coagulation Factor XIII (FXIII) can be categorized into severe and mild forms based on their genotype and phenotype. Heterozygous mutations occurring in F13A1 and F13B genes causing mild FXIII deficiency have been reported only in the last few years primarily because the mild FXIII deficiency patients are often asymptomatic unless exposed to some kind of a physical trauma. However, unlike mutations causing severe FXIII deficiency, many of these mutations have not been comprehensively chara… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
20
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 17 publications
(21 citation statements)
references
References 37 publications
1
20
0
Order By: Relevance
“…Two heterozygous mutations directly at the thrombin cleavage site, Arg37Gln and Arg37Pro, were expressed and were confirmed to lead to a FXIII-A type II deficiency with mildly decreased normal antigen levels but severely decreased FXIII activity. 34 It is not surprising, that FXIII activation is inhibited when the thrombin cleavage site itself is abolished by mutation. In our case, however, mutation of the neighbouring amino acid had a similar deleterious effect.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Two heterozygous mutations directly at the thrombin cleavage site, Arg37Gln and Arg37Pro, were expressed and were confirmed to lead to a FXIII-A type II deficiency with mildly decreased normal antigen levels but severely decreased FXIII activity. 34 It is not surprising, that FXIII activation is inhibited when the thrombin cleavage site itself is abolished by mutation. In our case, however, mutation of the neighbouring amino acid had a similar deleterious effect.…”
Section: Discussionmentioning
confidence: 99%
“…Structural data of the FXIII-A 2 dimer 12 and the AP-FXIII (28)(29)(30)(31)(32)(33)(34)(35)(36)(37) in complex with thrombin 13 were obtained from the Protein Data Bank (PDB-ID 1F13 and 1DE7; www.rcsb.org). Visualization of Pro36 within the molecular context and preparation of the figures was done with DeepView/Swiss-Pdb Viewer v.4.1.0 (www.expasy.org/spdbv/).…”
Section: Visualization Of Pro36 In the Molecular Contextmentioning
confidence: 99%
“…fibrinogen, BAPA and α-2 antiplasmin were considered since the endpoint FXIII activity assays dealt with these substrates. These binding regions had been determined by rigid docking studies we had earlier conducted and reported for fibrinogen and α-2 antiplasmin 52 .The putative BAPA binding region(s) were predicted by docking the structural coordinates of BAPA [5-(Biotinamido) pentylamine; Pubchem ID: CID 83906] that were downloaded from Pubchem database (as an SDF file and later converted to a PDB file on YASARA), onto the activated FXIII-A crystal structure (PDB ID: 4kty) downloaded from the protein database. Semi-flexible docking was performed with the Autodock function embedded in YASARA 52 .Finally these binding regions were mapped and highlighted on the FXIII-A subunit activation transition state intermediate models.…”
Section: Methodsmentioning
confidence: 99%
“…The structure of FXIIIa that was used as the receptor in the docking simulations was obtained in a pre-equilibrated state from the MD trajectory of the crystal structure of FXIIIa (PDB: 4KTY) reported in an earlier study [34,35]. The highest scoring docking poses for each aptamer was critically analyzed with respect to previously suggested fibrinogen (mainly alpha chain) and α2AP binding site residues as well as catalytically important active site residues [36]. Electrostatic surface potential of the FXIIIa was calculated and graphically depicted using the Adaptive Poisson-Boltzmann Solver integrated within YASARA.…”
Section: Molecular Modeling Of Fxiiia-aptamer Bindingmentioning
confidence: 99%